1997
DOI: 10.1023/a:1007346907864
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The serum alpha-tocopherol levels were determined in a group of 182 patients with hematological neoplasms: 87 lymphoid or myeloid leukemias, 65 lymphomas and 30 myelomas. The levels did not differ from those of controls, when compared either globally or for diagnosis. Low alpha-tocopherol serum levels were observed in 6 patients (3.3%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Battisti et al's study failed to observe any significant differences in vitamin E levels between gastric cancer patients and healthy individuals [39] . Marco et al studied vitamin E levels in patients with hematologic cancers and found no significant difference between the control and case groups [40] .…”
Section: Vitamin E Levelsmentioning
confidence: 99%
“…Battisti et al's study failed to observe any significant differences in vitamin E levels between gastric cancer patients and healthy individuals [39] . Marco et al studied vitamin E levels in patients with hematologic cancers and found no significant difference between the control and case groups [40] .…”
Section: Vitamin E Levelsmentioning
confidence: 99%